2005
DOI: 10.1081/copd-57580
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Quantifiable Symptom Assessment Tool for Patients with Chronic Bronchitis: The Chronic Bronchitis Symptoms Assessment Scale

Abstract: Clinical trials that rely solely on physiologic outcomes may underestimate effects of interventions on patients' symptoms and well-being. We sought to develop and validate an instrument to reliably assess symptom severity and frequency in therapeutic trials for patients with chronic bronchitis. We performed a series of psychometric studies that determined instrument content and assessed validity and reliability. The final version of the Chronic Bronchitis Symptoms Assessment Scale (CBSAS) comprised 15 scored i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Ideally, we would have used an additional cough-specific questionnaire. However, such questionnaires have not been specifically developed for, nor tested in COPD patients [11-15]. We used the SGRQ as the reference standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, we would have used an additional cough-specific questionnaire. However, such questionnaires have not been specifically developed for, nor tested in COPD patients [11-15]. We used the SGRQ as the reference standard.…”
Section: Methodsmentioning
confidence: 99%
“…One study found that only a small part (2%) of the variance in the scores of the St. George's Respiratory Questionnaire (SGRQ), a disease-specific health status questionnaire is explained by cough [2]. Several cough-specific health status questionnaires have been developed and validated in the general population presenting with cough but not necessarily with COPD [11-15]. Of these questionnaires only the Leicester Cough Questionnaire (LCQ) [16] is available in Dutch [17].…”
Section: Introductionmentioning
confidence: 99%
“…As secondary clinical outcomes, we evaluated changes in the three domains of the SGRQ, the Chronic Bronchitis Symptoms Assessment Scale (CBSAS), and the Short Form-36 Health Survey (SF-36). 16 , 17 We assessed lung function with postbronchodilator spirometry, systemic inflammation with serum C-reactive protein levels, and systemic oxidative stress with plasma 8-isoprostane levels. 18 We further assessed oxidative stress and biochemical efficacy of NAC, by measuring changes in thiol redox couples, GSH/GSH disulfide (GSSG) and cysteine/cystine (Cys/CySS) in plasma.…”
Section: Methodsmentioning
confidence: 99%
“…This instrument was developed to measure symptom and functional state in daily clinical practice. The most recent symptom questionnaire is the Chronic Bronchitis Symptoms Assessment Scale; this symptom questionnaire uses 16 items to capture symptoms in patients with COPD (83). The instrument demonstrated strong internal reliability (overall Cronbach's ␣ of 0.91), as well as statistically significant and moderate to strong associations with spirometry.…”
Section: Table 3 Overview Of Selected Instruments That Assess Signs mentioning
confidence: 99%